The Autobiographical Narrator in Doris Lessing's "The Children of Violence" - Rowlands, Kate (My University, 1989)
The problem of the shifting narrator in Doris Lessing's novel-series, "The Children of Violence" (1952-1969), is resolved by examining the series from the perspective of what has been seen as a second problem, the degree of autobiography. Even a cursory examination of Lessing's biography reveals parallels with so many of the major events (and even their locations) in Martha Quest's life, that it is reasonable to speak of the narrator as an autobiographical narrator.
The concept of an autobiographical narrator explains the verisimilitude of the portrait of the young girl, Martha Quest, growing into adulthood in Southern Africa. It also, however, explains Lessing's shift into interior monologue and symbolic language as her protagonist approaches her own age at the time of writing, since by the time she wrote the fourth novel in the series, Landlocked (1965), Lessing was steeped in an ancient mystic Islamic sect, Sufism, with its emphasis on the "teaching story".
Becoming conscious of her craft, and more particularly of the power of words and the sense of the fictional itself, Lessing, in her fifth novel, The Four-Gated City (1969), fuses fact and fiction to create a fictional documentary. She leaves behind her author/god role and introduces metafictional elements such as internal texts and specific vocabularies in order to keep the reader aware that he or she is reading a work of fiction.
In linking Lessing's life and consciousness with those of her narrator, I believe that I have found a way to demonstrate the unity of a series of novels in which the question of technique has remained problematic since the publication of the last novel, twenty years ago.
Keywords: English; English Language and Literature; English Language and Literature